Development Strategies of the Textile Industry of Uzbekistan (Texas Journal of Engineering and Technology, 2022)
The article assesses the results of the activities of the textile and clothing and knitwear industry of Uzbekistan for 2017-2020. The role of the industry in the development of the economy and industry, the growth of exports, the introduction of a cluster development model, and the provision of employment are shown. Development priorities are shown.